2006
DOI: 10.1002/tea.20177
|View full text |Cite
|
Sign up to set email alerts
|

Learning from students, inquiry into practice, and participation in professional communities: Beginning teachers' uneven progress toward equitable science teaching

Abstract: In this research project, we investigated two beginning secondary science teachers' efforts to learn to teach science in ways that build from and celebrate the ethnic, gender, linguistic, and academic diversity of their students. To do so, we followed Troy and Brian from their preservice teacher education experiences through their first year of teaching 8th grade physical science at local junior high schools. We also conducted a follow‐up observation and interview with each participant after he had moved past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 39 publications
4
60
0
4
Order By: Relevance
“…Researchers have found that early life experiences and conceptions of self can make identifying and critiquing long-held views about who students are and how they should be taught difficult (Brand & Glasson, 2004). Beginning teachers may embrace the notion of science and mathematics for all, but they still struggle to start instruction from the knowledge, interests, and experiences of their students (Bianchini & Cavazos, 2007;Simmons et al, 1999). Curriculum materials, course requirements, and school structures further constrain beginning teachers' efforts to engage all students in relevant and meaningful science or mathematics activities (Adams & Krockover, 1997;McGinnis, Parker, & Graeber, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that early life experiences and conceptions of self can make identifying and critiquing long-held views about who students are and how they should be taught difficult (Brand & Glasson, 2004). Beginning teachers may embrace the notion of science and mathematics for all, but they still struggle to start instruction from the knowledge, interests, and experiences of their students (Bianchini & Cavazos, 2007;Simmons et al, 1999). Curriculum materials, course requirements, and school structures further constrain beginning teachers' efforts to engage all students in relevant and meaningful science or mathematics activities (Adams & Krockover, 1997;McGinnis, Parker, & Graeber, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more contextual factors must be considered to encourage beginning teachers to be concentrating on students' engagement in meaningful science activities with the scaffolding by mentor teachers at school (Adams and Krockover, 1997;Choi et al, 2009). It has been reported that beginning teachers make effort to conduct the research into their practices of teaching science as inquiry in learning communities where they could interact with mentor teachers or educators (Bianchini and Cavazos, 2007;Roehrig and Luft, 2006;Kwak, 2009). More than anything else, all participants in this study showed their willingness that they would attend workshop of scientific inquiry if offered to have opportunities of reflecting on their prior views and practices to be integral with other factors rising in real context of teaching in the classroom.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…It is strongly recommended that we need to provide induction program where beginning teacher experience all kinds of success and struggles to be professionals in their science teaching. It might be best for beginning teachers to experience induction program housed at their schools, where they could become experts in science teaching while they interact with physical environment such as students, school context, and parents as well as other teachers (Bianchini and Cavazos, 2007).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Algunos de ellos indican que desde el comienzo de las experiencias de enseñanza los profesores practicantes (Bianchini & Cavazos, 2007, Eick & Dias, 2005Geddis & Roberts, 1998) y experimentados (Newberry, 2010) emprenden procesos de evaluación de sus estudiantes a fin de ajustar su enseñanza a sus intereses, habilidades y necesidades. Sin embargo, para los profesores noveles estos procesos implican mucho más tiempo y esfuerzos, puesto que sus ideas preconcebidas sobre los estudiantes suelen ser menos realistas -por no decir ingenuas-, en comparación con las de los experimentados (Grossman, 2005;Kagan & Tippins, 1991;Putnam & Borko, 1997/2000.…”
Section: Discusión Con Relación a La Literaturaunclassified
“…El escaso interés por el conocimiento de los estudiantes contrasta con los resultados de la literatura que revelan que las interacciones tempranas con los estudiantes son, quizás, el aspecto que más influencia el desarrollo profesional de los profesores practicantes de ciencias (Bianchini & Cavazos, 2007;Eick & Dias, 2005;Geddis & Roberts, 1998;Mulholland & Wallace, 2003, 2005. Estos emplean mucho tiempo y esfuerzo en llegar a conocer a sus estudiantes, a fin de ajustar su enseñanza y la gestión de sus clases a sus características cognitivas, físicas, sociales, culturales y emocionales.…”
Section: Introductionunclassified